Kinerja Industri Kecil Arang Tempurung Kelapa - Fadila, Nabila Dea; Rahmawati, Winda; Suharyatun, Siti; Haryanto, Agus (Jurnal Agricultural Biosystem Engineering, 2023)
Charcoal production from coconut shells is a promising alternative to utilize waste into charcoal products that have high economic value for a small industry. This study aims to determine the feasibility of a small-scale charcoal business that utilizes coconut shell waste. The research was carried out in January 2022 - June 2022 in the Tunas Mandiri coconut shell charcoal industry in Ambarawa Village, Pringsewu Regency. Field observations and sampling were carried out for three times. Parameters observed included process capacity, yield, characteristics of charcoal (density, moisture content, ash content, water absorption, calorific value), and economic analysis of the charcoal industry. The results showed that the Tunas Mandiri charcoal small industry produced two types of coconut shell charcoal, namely low quality charcoal and vacuum charcoal. Vacuum charcoal has good quality, namely water content 8.49%, ash content 2.04%, and calorific value 7475.00 cal/g (meeting the quality requirements of SNI No. 0258–79), while low quality charcoal has a moisture content of 29.92%, ash content of 3.72 %, and the calorific value is 6518.64 cal/g (does not meet the requirements of SNI No. 0258–79). The results showed that the shell charcoal business was economically feasible to run with a fairly high profit reaching Rp. 1,652,666.67 for each charcoal production process for 3-4 days. Keywords: Charcoal, Coconut Shell, Economy, Profit, Small-Scale Industry.